Porphyromonas gingivalis y fusobacterium nucleatum asociados a neoplasias malignas en cavidad oral. (2020)
Abstract Introduction. Porphyromonas gingivalis and Fusobacterium nucleatum are two anaerobic bacteria associated with etiology in periodontal disease. Its possible association with orodigestive neoplasms and colorectal cancer, respectively, has also been suggested. Objective. Bibliographically explore the scientific evidence about the possible association and its mechanisms between oral periodontopathogens and neoplasms in the oral cavity. Methodology. A systematic exporatory review of articles and reviews was carried out in PubMed, and bibliometric analysis in Scopus. This search was refined for the last 10 years from January 2009 to December 2019. Results. The evidence found in the articles shows that in the last 10 years, studies have been carried out aimed at using methodologies from traditional cultures to 16S rRNA metagenomic sequencing techniques to determine the relationship of periodontal pathogens in oral carcinogenesis. Addressing another area of the review, periodontal pathogens can influence oral carcinogenesis through the mechanisms of inhibition of apoptosis, activation of cell proliferation, cell promotion, invasion, induction of chronic inflammation and the production of carcinogens, analyzed in each author from the influence of the receptors, proteins, antibodies and immunoglobulins, which inhibit or exacerbate activities tending to the cecular functioning of the host. Conclusions. The association hypothesis has been seen in accordance with several studies in which, comparing cancer patients, a greater presence of these bacteria has been found. Porphyromonas gingivalis and periodontopathogenic Fusobacterium nucleatum are associated with malignant neoplasms in the oral cavity. Most of the studies have been done in humans, but there are experimental studies that support it. As in other infectious pathologies caused by viruses and even parasites, the studies carried out so far and according to the search criteria, support both by direct and indirect mechanisms the processes by which oral cancer can be induced, is to through the inhibitory action of apoptosis, activation of cell proliferation, promoting migration and cell invasion and inflammation and production of carcinogens. It is found that for gingival P they are inhibition of apoptosis, cell proliferation, migration and cell invasion and production of carcinogenic substances, while for F. nucleatum they are activation of cell proliferation, promotion of cell invasion and induction of chronic inflammation and production of cancderigenic substances. Much of the studies have been carried out in Europe, Asia, Australia and North America Key Words: Systematic exploratory review, oral cavity neoplasms, periodontitis and microbiome.